The Impact of Digital Economy on the Green Development Efficiency of the Logistics Industry – A Case from China Based on the Mediation Mechanism and Threshold Effect - Zhiqiang ZHAO; Lei ZHANG (Promet (Zagreb))
The logistics industry is full of expectations for ‘quality and efficiency’ due to the rapid development of the digital economy (DE). It is worth paying attention to whether the DE can reverse the rough development of the logistics industry and effectively promote the green development efficiency of the logistics industry (GLE). This paper empirically explores the impact of the DE on the GLE using mediation mechanisms and threshold effects, based on China’s inter-provincial panel data from 2011–2021. The empirical results indicate that the development of DE plays a significant role in promoting the GLE and can enhance the GLE through industrial structure upgrading. However, there is a masking effect of the labour productivity of the logistics industry on the impact of the DE on the GLE. The threshold test reveals that there is a threshold effect based on the scale of the logistics industry and the level of scientific and technological innovation in the impact of the DE on the GLE.